Gender, property rights, and natural resources - Meinzen-Dick, Ruth S.; Brown, Lynn R.; Feldstein, Hilary Sims; Quisumbing, Agnes R. (International Food Policy Research Institute, 1997)
This paper analyzes the ways in which gender issues affect property rights and the use of natural resources in developing countries. It examines the informal practices of resource use, usually involving multiple uses by multiple users. Traditional systems of access to land, water, and trees reflect complex dynamics among community members that must be understood in order to design successful policy interventions concerning natural resources. Drawing on examples from developing countries worldwide, the paper identifies broad patterns in how property rights are determined. It discusses the effects of privatization and commoditization of resources, and it identifies key issues to consider in the context of proposed resource management programs.